1936
DOI: 10.1042/bj0301970
|View full text |Cite
|
Sign up to set email alerts
|

The activation of the male sex hormones. I

Abstract: I. The activation of testosterone by the addition of organic acids. IT is well known that in the rat test testosterone exhibits a greater activity than androsterone, especially on the seminal vesicles of castrated rats. As we have recently shown [1936, 1, 2] this only applies to oily solutions of testosterone; testosterone is, strangely enough, hardly active when dissolved in paraffin oil or in aqueous solutions of glycerol. We found, however, that after the addition of certain carboxylic acids, especially of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1937
1937
1981
1981

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Since the action of testosterone propionate is a delayed one (Miescher, Wettstein and Tschopp [1936], Parkes [1936]), it was decided to examine the effect of two injections in 12 hours, and to test these against a slightly larger amount of cestrone. It was found that when '294 Hain …”
Section: Resultsmentioning
confidence: 99%
“…Since the action of testosterone propionate is a delayed one (Miescher, Wettstein and Tschopp [1936], Parkes [1936]), it was decided to examine the effect of two injections in 12 hours, and to test these against a slightly larger amount of cestrone. It was found that when '294 Hain …”
Section: Resultsmentioning
confidence: 99%
“…From these figures it would seem that 20 mg. of testosterone produces a response of the same order as 2 y of cestrone, and 20 mg. trans-dehydroandrosterone or andro-stenedione one similar to 10 y cestrone. Other experiments with these compounds, carried out with 3 injections on alternate days, suggest that under these conditions the addition of palmitic acid to the solution leads to an increase in the effectiveness of the dose, but to a lesser extent than is found in rats [Miescher, Tschopp, and Wettstein, 1936]. The most cestrogenic of the compounds, therefore, seems to be about one two-thousandth as active as cestrone.…”
Section: Introductionmentioning
confidence: 88%
“…In this respect, therefore, these two male hormone substances may be considered to have certain properties akin to those of progesterone but also others differing from them. The apparent capacity of testosterone to inhibit the cestrous cycle changes in the vagina of the adult female rat [Robson, 1936;Miescher and Tschopp, 1936] may also depend on its power to modify the action of cestrone in the direction of mucification. Selye, McEuen, and Collip [1936] have described stimulation of the mammary glands of the gonadectomised rat by administration of testosterone, while Wells and Moore [1936] have stated that spermatogenesis may be initiated in the quiescent ground squirrel by injection of testosterone.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds were dissolved in arachis oil, and injected sub cutaneously. At the time these experiments were being carried out, it was demonstrated by Miescher, Wettstein, and Tschopp (1936) that the activity of testosterone could be much increased by adding fatty acids to the oil solution, a result almost certainly brought about by retardation of absorption. In certain cases, therefore, a total of 1 gm.…”
Section: T Ech N Iqu Ementioning
confidence: 99%